The correlation of plasma lipid levels with susceptibility of inbred laboratory mice to experimental trypanosoma congolense infection. - Hassan, M.A. (University of Nairobi, 2003)
Mammalian hosts of African trypanosomes show marked differences in susceptibility to infection with Trypanosoma congolense as judged by survival time, anaemia, and levels of parasitaemia. For instance, the N'Dama cattle and the West African shorthorn breeds are resistant to Trypanosomiasis whereas the Zebu and European cattle breeds are in general, more susceptible. Similarly, C57BLl6J mice are relatively resistant to Trypanosoma congolense infection than BALB/c and A/J strains. Because bloodstream trypanosomes cannot synthesize lipids de novo, and that resistant animals (cattle, buffalo, and mice) have lower plasma lipid levels than the susceptible ones, it was hypothesized in this work, that plasma lipids influence progression of Trypanosomiasis. Furthermore, genetic studies have mapped the quantitative trait loci (QTL) for trypanotolerance and plasma lipid levels in mice to the same region. Finally, studies indicate that the genes that control plasma lipid levels are differentially expressed in resistant versus susceptible strains during Trypanosomiasis To investigate this hypothesis, the plasma lipid levels of C57BLl6J, A/J, and BALB/c inbred mice were manipulated by feeding them (ad libitum) on calorie matched low (5.16%) or high (23.45%) fat diets. The diets were designated low or high fat when compared to the basal (10% fat) laboratory mouse diet. Mice were then infected with T. congolense. Parasitaemia, body weight, plasma lipids and anaemia were then monitored. Results indicate that the mice on the high fat diet suffered more weight loss and had low parasitaemia than those on the low fat diet. Hence it can be concluded that, high plasma lipid levels do not aggravate Trypanosomiasis.